Molecular dynamics simulation of poly(3‐hexylthiophene) helical structure In Vacuo and in amorphous polymer surrounding. Issue 23 (15th September 2016) - Borzdun, Natalia I.; Larin, Sergey V.; Falkovich, Stanislav G.; Nazarychev, Victor M.; Volgin, Igor V.; Yakimansky, Alexander V.; Lyulin, Alexey V.; Negi, Vikas; Bobbert, Peter A.; Lyulin, Sergey V.
ABSTRACT: The stability of poly(3‐hexylthiophene) (P3HT) helical structure has been investigated in vacuo and in amorphous polymer surrounding via molecular dynamics‐based simulations at temperatures below and above the P3HT melting point. The results show that the helical chain remains stable at room temperature both in vacuo and in amorphous surrounding, and promptly loses its structure at elevated temperatures. However, the amorphous surrounding inhibits the destruction of the helix at higher temperatures. In addition, it is shown that the electrostatic interactions do not significantly affect the stability of the helical structure. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2016, 54, 2448–2456 Abstract : The stability of poly(3‐hexylthiophene) (P3HT) helical structure is investigated in vacuo and in amorphous polymer surrounding via molecular dynamics simulations at temperatures below and above the P3HT melting point. The helical chain remains stable at room temperature and promptly loses its structure at elevated temperatures. The amorphous surrounding inhibits the destruction of the helix at higher temperatures and the electrostatic interactions do not significantly affect the stability of the helical structure.